Rola controllera w tworzeniu systemu ograniczenia ryzyka w działalności gospodarczej na przykładzie wydawnictwa - Kotapski, Roman (Creating the Risk's System at Publishing Company and a Role of the Specialist Of Management Accounting at This System, 2007)
The risk is a part of running business. If you have some good tools and procedures you can decrease loss of company while planning your products. You have to have tools: a project of a book, cost estimation of a book and a procedure of qualified project's for production. The specialist of management accounting can be very important during implementation of the risk's system in a company
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 292-301